ESPEN guideline on home parenteral nutrition. Issue 6 (June 2020) - Pironi, Loris; Boeykens, Kurt; Bozzetti, Federico; Joly, Francisca; Klek, Stanislaw; Lal, Simon; Lichota, Marek; Mühlebach, Stefan; Van Gossum, Andre; Wanten, Geert; Wheatley, Carolyn; Bischoff, Stephan C.
Summary: This guideline will inform physicians, nurses, dieticians, pharmacists, caregivers and other home parenteral nutrition (HPN) providers, as well as healthcare administrators and policy makers, about appropriate and safe HPN provision. This guideline will also inform patients requiring HPN. The guideline is based on previous published guidelines and provides an update of current evidence and expert opinion; it consists of 71 recommendations that address the indications for HPN, central venous access device (CVAD) and infusion pump, infusion line and CVAD site care, nutritional admixtures, program monitoring and management. Meta-analyses, systematic reviews and single clinical trials based on clinical questions were searched according to the PICO format. The evidence was evaluated and used to develop clinical recommendations implementing Scottish Intercollegiate Guidelines Network methodology. The guideline was commissioned and financially supported by ESPEN and members of the guideline group were selected by ESPEN.